The Alteration of M6A-Tagged Transcript Profiles in the Retina of Rats After Traumatic Optic Neuropathy - Qu, Xiaolin; Zhu, Kaixin; Li, Zhenxing; Zhang, Danfeng; Hou, Lijun (Frontiers in Genetics, 2021)
Messager RNA (mRNA) can be modified in a variety of ways, among which the modification of N6-methyladenosine(m6A) is one of the most common one. Recent studies have found that the m6A modification in mRNA can functionally regulate the splicing, localization, translation and stability of mRNA. However, the roles of m6A modification in traumatic optic neuropathy (TON) are still unknown. Herein, we detected the expression of m6A-related genes via quantitative real-time PCR (qRT-PCR) and performed methylated RNA immunoprecipitation sequencing (MeRIP-seq) as well as RNA-sequencing to analyze the alteration profiles of m6A modification after TON. The results showed that the expression of m6A-related genes (METTL3, WTAP, FTO and ALKBH5) were all upregulated after TON. In all, 2810 m6A peaks were differentially upregulated and 689 m6A peaks were downregulated. In addition, the hypermethylated and hypomethylated profiles of mRNA transcripts were also identified. To sum up, our study revealed the differentially expressed m6A modification in the early stage of TON, which may provide novel insights into the mechanism and treatment of TON.